The Challenges of E-Learning Implementation During the Covid-19 Pandemic in Senior High School - Fitra Delita (MO.RI Publishing, 2021)
The Covid-19 pandemic has brought changes in various fields of life, including education. The purpose of this study was to describe the challenges faced by teachers and students in e-learning in the Covid-19 pandemic. This study uses a qualitative approach through data collection using an online questionnaire with Google form and structure interview by phone. Respondents consisted of 163 geography teachers and 104 students at the high school level in North Sumatra Province. This data is then analyzed descriptively in the form of scores and percentages. The result showed that the challenges faced by teachers were especially expertise, preparation for learning, access to e-learning, management of learning in the e-learning platform, supporting facilities, and time effectiveness in e-learning. While the challenges faced by students include understanding the material, access to the learning process, discipline in online learning, learning support facilities for e-learning, and the conditions of the learning environment. Pandemi Covid-19 membawa perubahan pada berbagai bidang kehidupan termasuk bidang pendidikan. Tujuan penelitian ini adalah untuk mendeskripsikan tantangan yang dihadapi guru dan siswa pada e-learning di masa pandemi. Penelitian ini menggunakan pendekatan kualitatif melalui pengumpulan data dengan kuesioner online menggunakan Google form dan wawancara terstruktur melalui telepon. Responden terdiri atas 163 guru geografi dan 104 siswa Sekolah Menengah Atas di Provinsi Sumatera Utara. Data dianalisis secara deskriptif dalam bentuk skor dan persentase. Hasil penelitian menunjukkan bahwa tantangan yang dihadapi guru antara lain keahlian, persiapan pembelajaran, akses e-learning, pengelolaan pembelajaran dalam platform e-learning, fasilitas pendukung dan efektifitas waktu. Sedangkan tantangan yang dihadapi siswa meliputi pemahaman terhadap materi, akses e-learning, disiplin dalam e-learning, fasilitas pendukung dan kondisi lingkungan pembelajaran.